Constraints in Adopting Improved Chickpea Cultivation Practices in Ballia, Uttar Pradesh (Indian Journal of Extension Education, 2025)
Despite favourable agro-climatic conditions in eastern Uttar Pradesh, chickpea productivity remains below potential due to multiple adoption barriers. This study investigated the constraints faced by chickpea growers in Ballia district, Uttar Pradesh, during the Rabi season of 2024–25. Using multistage random sampling, 160 farmers from four blocks and sixteen villages were surveyed with structured interviews. The most pressing constraint was the non-availability of agricultural inputs at the proper time, followed by knowledge related gaps such as a lack of information about improved chickpea varieties and a lack of training in scientific chickpea production. Economic factors such as the high cost of seed, fertilisers, insecticides, and implements, and institutional issues like the non-availability of required seeds in cooperative societies also ranked high. Environmental and social issues–particularly the grazing animal problem and labour shortages during peak seasons further complicated technology adoption. Lower-ranked but still relevant constraints included limited exposure to demonstrations, poor market access, and gender barriers in extension outreach. These findings highlight the complex interplay of technical, economic, institutional, and environmental factors in adoption behaviour. The study recommends a multi-dimensional approach involving timely input delivery, capacity building, improved infrastructure, and targeted policy interventions to enhance chickpea productivity and sustainable adoption of improved cultivation practices.